Rural India real India - Thingalaya, N. K. (ed.) (Bombay, 1986)
This book contains the papers presented at a national seminar organised by a nationalised bank. A number of administrators of rural development, representatives of financial institutions and a few eminent economists who have contributed considerably towards policy formulation for rural development in India participated in the Seminar. The problems relating to rural India and the various developmental pro grammes initiated in the recent years are discussed Besides the ed papers, the deliberations have been very ably presented by apporteurs who are experts in their own fields. For three days, 80 participants met in a typical rural setting to analyse
Keywords: Rural development India